Association Between Symptom Duration and Patient‐Reported Outcomes Before and After Hip Replacement Surgery. Issue 3 (27th February 2020) - Lau, Yiu‐Shing; Harrison, Mark; Sutton, Matt
Abstract : Objective: Patients experience discomfort and compromised quality of life while waiting for hip replacement. Symptom duration may affect quality of life attained following surgery. We undertook this study to investigate the impact of symptom duration on patient‐reported postsurgical outcomes from hip replacement surgery. Methods: National observational data collected before and after hip replacement surgery in England between 2009 and 2016 were used to investigate determinants of symptom duration prior to surgery and the relationship between symptom duration and presurgical and postsurgical patient‐reported outcomes. Multivariable linear regression models were used to estimate associations between patient‐reported outcomes and symptom duration, controlling for a range of covariates. Results: The sample included 209, 192 patients; most (69%) experienced symptoms for 1–5 years. A few patients (14%) experienced symptoms for <1 year, for longer than 5 years (6–10 years [11%]), or for >10 years (5%). Symptom duration decreased overall over the studied time period and was shorter among patients who were male, older, and from areas of lesser deprivation. Patients with a symptom duration <1 year had better postsurgical pain and function outcomes (Oxford Hip Score [OHS] 0.875 [95% confidence interval (95% CI) 0.777, 0.973]) than those with 1–5 years symptom duration in an adjusted model. Conversely, those with symptom duration >5 years had increasingly poorer postsurgical outcomes (OHS –0.730 [95% CI –0.847, –0.613] for those with disease duration 6–10 years and OHS –1.112 [95% CI –1.278, –0.946] for those with disease duration >10 years). Conclusion: Symptom duration prior to hip replacement has become more standardized in England over time. However, increasing duration remains a significant predictor of poorer outcomes after surgery.